Identidades na perspectiva da educação infantil da Escola Estadual Quilombola Maria de Arruda Muller – Quilombo Abolição/MT - França, Michele Corrêa de (2019)
This study presents the results of an ethnographic research, complemented by action research, carried out at the Quilombola Maria de Arruda Muller State School, located in the Quilombola Abolição Community, in Santo Antônio de Leverger-MT. Its main objective is to understand how children of Quilombola Kindergarten perceive Quilombo in their identity aspects and what is the perspective of an education for the affirmation of their identity, from the materiality of the curricular proposal for Quilombola School Education in Mato Grosso, as an important educational public policy. Theoretically, this study is supported by Arroyo (2001), Castilho (2011 and 2016), Cuche (1999), Cerisara (1999), Geertz (2008), Hall (2005), Leite (1999; 2005 and 2008), Moura (2001), Munanga (2004; 2009 and 2012), Rosemberg (2003), Silva, Hall and Woodward (2014) and Thiollent (1986). The instruments used for data collection consisted of: participant observation, semi-structured interview, Dolls Test and Image Technique, record in the field notebook, documents and photographs. The results showed the absence of a positive reference for the black and quilombola children, who early suffer and crystallize racial prejudices widespread in the mass communication educational processes that affect them, added to the silence of the implemented pedagogical proposal. Moreover, they demonstrated that the confrontation with this situation is the inclusion of the specificities of Quilombola School Education in the pedagogical proposal of quilombos schools in all stages of Basic Education, in this specific case in Early Childhood Education. The research also revealed that the educational practices that problematize the black and quilombola identities can contribute, in order to subsidize the teaching practice in the systematization of the traditional knowledge that feeds the quilombola school curriculum and that the biggest challenges are related to obtaining material specific didactic, material and financial resources.